Sub-Antarctic Freshwater Invertebrate Thermal Tolerances: An Assessment of Critical Thermal Limits and Behavioral Responses - Javier Rendoll-Cárcamo; Tamara Contador; Peter Convey; James Kennedy (Insects, 2020)
Physiological thermal limits of organisms are linked to their geographic distribution. The assessment of such limits can provide valuable insights when monitoring for environmental thermal alterations. Using the dynamic critical thermal method (CTM), we assessed the upper (CTmax) and lower (CTmin) thermal limits of three freshwater macroinvertebrate taxa with restricted low elevation distribution (20 m a.s.l.) and three taxa restricted to upper elevations (480 and 700 m a.s.l.) in the Magellanic sub-Antarctic ecoregion of southern Chile. In general terms, macroinvertebrates restricted to lower altitudinal ranges possess a broader thermal tolerance than those restricted to higher elevations. Upper and lower thermal limits are significantly different between taxa throughout the altitudinal gradient. Data presented here suggest that freshwater macroinvertebrates restricted to upper altitudinal ranges may be useful indicators of thermal alteration in their habitats, due to their relatively low tolerance to increasing temperatures and the ease with which behavioral responses can be detected.